Slc20a2-Deficient Mice Exhibit Multisystem Abnormalities and Impaired Spatial Learning Memory and Sensorimotor Gating but Normal Motor Coordination Abilities - Ren, Yaqiong; Shen, Yuqi; Si, Nuo; Fan, Shiqi; Zhang, Yi; Xu, Wanhai; Shi, Lei; Zhang, Xue (Frontiers in Genetics, 2021)
Background: Primary familial brain calcification (PFBC, OMIM#213600), also known as Fahr's disease, is a rare autosomal dominant or recessive neurodegenerative disorder characterized by bilateral and symmetrical microvascular calcifications affecting multiple brain regions, particularly the basal ganglia (globus pallidus, caudate nucleus, and putamen) and thalamus. The most common clinical manifestations include cognitive impairment, neuropsychiatric signs, and movement disorders. Loss-of-function mutations in SLC20A2 are the major genetic causes of PFBC. Objective: This study aimed to investigate whether Slc20a2 knockout mice could recapitulate the dynamic processes and patterns of brain calcification and neurological symptoms in patients with PFBC. We comprehensively evaluated brain calcifications and PFBC-related behavioral abnormalities in Slc20a2-deficient mice. Methods: Brain calcifications were analyzed using classic calcium-phosphate staining methods. Morris water maze, Y-maze, and fear conditioning paradigms were used to evaluate long-term spatial learning memory, working memory, and episodic memory, respectively. Sensorimotor gating was mainly assessed using the prepulse inhibition of the startle reflex program. Spontaneous locomotor activity and motor coordination abilities were evaluated using the spontaneous activity chamber, cylinder test, accelerating rotor-rod, and narrowing balance beam tests. Results: Slc20a2 homozygous knockout (Slc20a2-HO) mice showed congenital and global developmental delay, lean body mass, skeletal malformation, and a high proportion of unilateral or bilateral eye defects. Brain calcifications were detected in the hypothalamus, ventral thalamus, and midbrain early at postnatal day 80 in Slc20a2-HO mice, but were seldom found in Slc20a2 heterozygous knockout (Slc20a2-HE) mice, even at extremely old age. Slc20a2-HO mice exhibited spatial learning memory impairments and sensorimotor gating deficits, while exhibiting normal working and episodic memories. The general locomotor activity, motor balance, and coordination abilities were not statistically different between Slc20a2-HO and wild-type mice after adjusting for body weight, which was a major confounding factor in our motor function evaluations. Conclusion: The human PFBC-related phenotypes were highly similar to those in Slc20a2-HO mice. Therefore, Slc20a2-HO mice might be suitable for future evaluation of neuropharmacological intervention strategies targeting cognitive and neuropsychiatric impairments.